The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1111/j.1476-5381.1996.tb16687.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional, endogenously expressed 5‐hydroxytryptamine 5‐ht7 receptors in human vascular smooth muscle cells

Abstract: Human uterine artery smooth muscle cells in culture were shown to express constitutively both 5-ht7 receptor mRNA and 5-ht7-like receptors functionally linked to cyclic AMP formation. 5-Carboxamidotryptamine (5-CT) and 5-HT enhanced forskolin-stimulated cyclic AMP accumulation in these cells, with pEC50 values of 7.12 and 6.25, sumatriptan being very weakly active. Both methiothepin (0.1 gM) and clozapine (1 gM), but not the 5-HT4-receptor antagonist, SDZ 205-557 (10 gM) antagonized the effects of 5-CT. In rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
39
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 6 publications
4
39
0
Order By: Relevance
“…The brain, heart, small intestine and testis contained the highest levels of expression. Due to the presence of h5-HT 7(a) mRNA in the vasculature (Bard et al 1993;Jasper et al 1997;Schoeffter et al 1996;Ullmer et al 1995), it is tempting to speculate that the ubiquitous expression of h5-HT 7(a) mRNA may result in part from mRNA derived from the vasculature of the tissue. Thus far, the h5-HT 7(b) splice variant is reportedly expressed in multiple brain regions, aorta, small intestine, stomach and spleen (Heidmann et al 1997;Jasper et al 1997).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The brain, heart, small intestine and testis contained the highest levels of expression. Due to the presence of h5-HT 7(a) mRNA in the vasculature (Bard et al 1993;Jasper et al 1997;Schoeffter et al 1996;Ullmer et al 1995), it is tempting to speculate that the ubiquitous expression of h5-HT 7(a) mRNA may result in part from mRNA derived from the vasculature of the tissue. Thus far, the h5-HT 7(b) splice variant is reportedly expressed in multiple brain regions, aorta, small intestine, stomach and spleen (Heidmann et al 1997;Jasper et al 1997).…”
Section: Discussionmentioning
confidence: 97%
“…Diverse physiological roles of 5-HT 7 receptors have been implicated in multiple organ systems, such as the cardiovascular system (De Vries et al 1999;Schoeffter et al 1996;Terron and Falcon-Neri 1999;Ullmer et al 1995;Villalon et al 1997), CNS (Cohen et al 1999;Eglen et al 1997;Héry et al 1997;Saxena et al 1998) and digestive tract (Carter et al 1995). Despite the increased understanding of the putative physiological roles of the 5-HT 7 receptor (see Eglen et al 1997 for review), little is known about which splice variants are mediating these effects.…”
Section: Introductionmentioning
confidence: 98%
“…The variants encode receptors that have slightly different lengths of the C termini, but with no detectable difference in tissue distributions or functional couplings (13). The 5-HT 7 receptor has also been detected in the periphery, where it is found primarily in smooth muscle cells of blood vessels (2,14), but also in the gastrointestinal tract (2).…”
mentioning
confidence: 99%
“…Early evidence supported by the pharmacological profile suggested that the 5-HT 7 receptor mediates the 5-HT-induced phase resetting of the circadian clock within the suprachiasmatic nucleus of the hypothalamus (1). The ability of 5-HT 7 receptors to mediate smooth muscle relaxation (14,20) has led to the suggestion that ligands may have therapeutic value in migraine (21). The 5-HT 7 receptor has also been implicated in endocrine regulation and neuropsychiatric disorders (22).…”
mentioning
confidence: 99%
“…In addition, the expression of the 5-HT 7 receptor in the suprachiasmatic nucleus (SCN) and the ability of serotonin and cAMP to advance the mammalian circadian rhythm indicates that 5-HT 7 plays an important role in circadian physiology (10,14,15). 5-HT 7 receptors are also expressed in glial cells (16,17) and at lower levels in peripheral tissues including the spleen, intestine, and vascular smooth muscle (7)(8)(9)18).…”
mentioning
confidence: 99%